Spacers-induced structural diversity of cobalt coordination polymers based on "V"-type dipyridylamide and dicarboxylic ligands: Fluorescent, magnetic and photocatalytic properties. (18th April 2017) - Liu, Guo-Cheng; Yu, Hui-Xuan; Lin, Hong-Yan; Wang, Xiu-Li; Li, Xiao-Wu
Graphical abstract: Six "V"-type dipyridylamide-based compounds have been hydrothermally synthesized and structural directed by spacers, which show different fluorescent, magnetic and photocatalytic properties. Abstract: To investigate the effect of the spacers of "V"-type dipyridylamide and dicarboxylic ligands on the structural diversity of Co II coordination polymers, [Co(L 1 )(5-CH3 -1, 3-bdc)]·2H2 O (1 ) [Co(L 2 )(5-CH3 -1, 3-bdc)(H2 O)]·H2 O (2 ) [Co(L 2 )(5-NO2 -1, 3-bdc)(H2 O)]·H2 O (3 ) [Co(L 2 )(1, 3-bdc)(H2 O)]·H2 O (4 ) [Co(L 2 )(4, 4′-oba)]·3H2 O (5 ) and L 2 ·2H2 O (6 ) [L 1  = N, N′-bis(pyridine-3-yl)pyridine-2, 6-dicarboxamide, L 2  = N, N′-bis(pyridine-3-yl)-5-methylisophthalic dicarboxamide, 5-CH3 -1, 3-H2 bdc = 5-methylisophthalic acid, 5-NO2 -1, 3-H2 bdc = 5-nitroisophthalic acid, 1, 3-H2 bdc = 1, 3-benzenedicarboxylic acid, 4, 4′-H2 oba = 4, 4′-oxybis(benzoic acid)] have been hydrothermally synthesized. Complexes1 –5 were characterized by IR spectroscopy, thermal analysis, TG and X-ray single-crystal diffraction. Complex1 is a 2D structure based on (4, 4)-connected [Co(5-CH3 -1, 3-bdc)] network and [Co(L 1 )] helixes. Complexes2 –4 feature isostructural 2D networks derived from Co-dicarboxylate linear chains and [Co(L 2 )] helixes. Complex5 show 1D tubular structure constructed by two parrelled [Co(4, 4′-oba)] linear chains and [Co(L 2 )] loops. Compound6 is a 3D supramolecular structure extended by L 2 ligands and water molecules. The effect of the spacers of "V"-type dipyridylamide and dicarboxylic ligands on the structures of the title compounds were discussed. The magnetic property of1, the fluorescent behaviors of1 –6 and photocatalytic properties of1 –5 under UV irradiation were studied.